Nuconarius gen. n. and Hengconarius gen. n., two new genera of Coelotinae (Araneae, Agelenidae) spiders from Southwest China - Li, Bing; Zhao, Zhe; Zhang, Chuntian; Li, Shuqiang (Zootaxa, 2018)
Two new genera of Coelotinae F.O.Pickard-Cambridge, 1893 from Southwest China are described: Nuconarius Z. Zhao & S. Li gen. n. and Hengconarius Z. Zhao & S. Li gen. n. The type species of Nuconarius Z. Zhao & S. Li gen. n. is N. brevipatellatus Z. Zhao & S. Li sp. n. and two additional species also belong here: N. capitulatus (Wang, 2003) comb. n. and N. pseudocapitulatus (Wang, 2003) comb. n. The type species of Hengconarius Z. Zhao & S. Li gen. n. is H. exilis (Zhang, Zhu & Wang, 2005) comb. n. and this genus includes seven additional species: H. dedaensis Z. Zhao & S. Li sp. n., H. falcatus (Xu & Li, 2006) comb. n., H. incertus (Wang, 2003) comb. n., H. latusincertus (Wang, Griswold & Miller, 2010) comb. n., H. longipalpus Z. Zhao & S. Li sp. n., H. longpuensis Z. Zhao & S. Li sp. n. and H. pseudobrunneus (Wang, 2003) comb. n. All species are from Southwest China and their distributions are mapped. New combinations are all ex-Draconarius Ovtchinnikov, 1999. The male of N. capitulatus is matched correctly for the first time and the DNA barcodes of all species are documented.